Design of contract net protocol-based distributed image processing system. (1st January 2014) - Prajapati, Harshad B.; Shah, Vipul A.
In the current era of large scale distributed computing, users voluntarily donate computation power of their idle computers or desktop machines. However, there is an urgent need of a utility-based distributed problem solving environment to attract more users. Related to applying the utility concept, we are working on design and implementation of a distributed image processing system that uses: 1) contract net protocol for task assignment; 2) concept of utility-based distributed computing; 3) task graph concept for application design. In this paper, we present our results of the design aspects of the system. We propose the design of contract net protocol-based distributed image processing system and analyse characteristics of the proposed system. We evaluate and select available options for implementation of the system. The proposed system allows transparent execution of task graph-based applications in a distributed environment.